Assessing the proximate compositions of indigenous forage species in Yemen’s pastoral rangelands - Louhaichi, Mounir; Al-koor, Basel; Gamoun, Mouldi; Abdurahman, Anwar; Hassan, Sawsan (De Gruyter, 2024)
Plant diversity in southern Yemen is crucial for maintaining rangeland ecosystem functions. This diversity contributes to the resilience of local pastoral communities, by providing essential forage and resources. However, high stocking density has led to the overuse of palatable species, resulting in increased competition for forage. This study evaluates the nutritional value of 25 indigenous forage species from the natural rangelands of Lahij Governorate. Significant variations were observed among the Forage species, with moisture content ranging from 4 to 39.6%, crude protein from 5.5 to 21.4%, non-fiber carbohydrates from 31.8 to 66.4%, crude fiber from 8.3 to 42.65%, and ash content from 9.2 to 34.6%. Clitoria ternatea, Lycium barbarum, Senegalia mellifera, Vigna sinensis, Albizia lebbeck, and Acacia trees with crude protein content higher than 16% showed substantial potential as livestock feed due to their favorable proximate compositions. Incorporating these high-potential species into regular livestock diets could significantly enhance the sustainability and productivity of pastoral systems in southern Yemen, addressing the current fodder shortage.